A Kantian Moral Response to Poverty - Igneski, Violetta (Ethical theory and moral practice, 2023)
Poverty is a global problem that is not only about material deprivation, but also a lack of agency and power. A Kantian response, with its focus on supporting the conditions of agency and empowerment, seems well suited to providing individuals with normative guidance on what their obligations are. The problem is that the guidance one finds within Kantian ethics is focused on the individual duty to aid or the duty to rescue, both of which have limited application in the context of a complex, wide-ranging and structural problem like poverty. Individuals, on their own, are unable to end poverty and they cannot adopt this as an end of theirs. But if they get together with enough others, things look a lot more promising. Even though a fully Kantian response to poverty requires exploring his legal philosophy and the role of the state, I focus here on the moral obligations of individuals, particularly the idea that by joining together we have increased capacity to respond and make a difference. If we start with certain assumptions about capacity and agency; namely that "ought implies can" and "only agents are duty-bearers", it is not clear that collectives that are not (yet) agents—such as "humanity" or "the affluent" or "the poor"—are possible duty-bearers. The aim of this paper is to support a more expansive account of Kantian moral obligations in which unstructured collectives have moral duties and their individual members have duties both to help form effective collective agents, and also to fulfill their shares of the collective duty to end poverty.